2022
DOI: 10.3389/fpsyg.2022.911841
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Effect of Perceived Social Support on School Readiness, Mental Wellbeing, and Self-Esteem: Mediating Role of Psychological Resilience

Abstract: Objective of this study is to investigate the impact of perceived social support on the self-esteem, mental wellbeing, and school readiness of left-behind (LB) children. It further aims at understanding the mediating role of psychological resilience between the relationships of perceived social support and self-esteem, mental wellbeing, and school readiness. For this purpose, population frame of the LB children between the ages of 8–12 years in Mainland China was taken. The sample size of 335 was taken to reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
(139 reference statements)
1
0
0
Order By: Relevance
“…This study also found that the sense of security among LBC played a mediating role between negative life events and life satisfaction, which was consistent with the findings of Rowe et al (2013). LBC have a sense of powerlessness in coping with negative life events and may adopt a negative attribution bias (Shi, 2022). They perceive negative life events as uncontrollable and anticipate them.…”
Section: Discussionsupporting
confidence: 87%
“…This study also found that the sense of security among LBC played a mediating role between negative life events and life satisfaction, which was consistent with the findings of Rowe et al (2013). LBC have a sense of powerlessness in coping with negative life events and may adopt a negative attribution bias (Shi, 2022). They perceive negative life events as uncontrollable and anticipate them.…”
Section: Discussionsupporting
confidence: 87%
“…Social support has been described as a protective factor against mental health problems (Mei et al, 2022) and stigma (Friedman et al, 2014). It has been associated with better adaptation to stressful factors (Schmitt et al, 2014) and with resilience (Salim et al, 2019), as it improves selfefficacy (Wang et al, 2020), self-esteem (Shi, 2022), and life satisfaction (Alshammari et al, 2021). In fact, lack of social support appears to be associated with more severe psychiatric symptoms (Morina et al, 2021).…”
mentioning
confidence: 99%